Analysis on Mode Transition in a Dual-Mode Scramjet Combustor. Issue 1 (2nd January 2018) - Li, Jianping; Jin, Rongjia; Jiao, Guiqian; Song, Wenyan
ABSTRACT: An ignition combustion test of different combustor configurations and different fuel equivalence ratios was carried out in a condition of total temperature at 880 K, total pressure at 8 atm, and Mach number of 2.0 in regards to dual-mode combustor. There are three combustor configurations that are dual-mode combustors with double cavity flame holder. Hydrogen is injected in the first cavity while kerosene is injected in front of the first cavity. Hydrogen, being a pilot flame, was the first to be ignited by the spark, then kerosene was ignited by hydrogen. After that, injection of hydrogen was stopped and sole kerosene was kept burning steadily. The distribution of other airflow parameters in the combustor was obtained by calculating with a 1D analysis method; the influence of combustor configuration and fuel equivalence ratio to combustion mode transition was analyzed. The results indicated that the gradual transition of combustion mode in the combustor from supersonic combustion mode to subsonic combustion mode was accompanied by increasing the fuel equivalence ratio. The disturbance arising from wall pressure rise of the combustor was gradually moved upstream. The subsonic combustion area in Model 2 was moved by 60 mm upstream when compared with that in Model 1, which was basically in conformity with the distance that the initial position of the first cavity in Model 2 was moved by 58 mm forward. When the fuel equivalence ratio was equal, the length of subsonic combustion areas in the two models was basically unchanged. In the case of combined combustion of hydrogen and kerosene, the pressure disturbance had been spread upstream and arrived at the entrance to the combustor; thus, the inlet Mach number condition of the entrance to the combustor was damaged. The damage to the condition of the entrance to the combustor was more serious to some extent in Model 2 due to antedisplacement of the first cavity when compared with that in Model 1.